The influence of sports lottery purchase on sports participation behavior - Ching-Te, Lin; Tso- Yen, Mao; Cheng-Feng, Ho; Chin-Cheng, Yang; Chih-Chien, Shen (SPORT TK-EuroAmerican Journal of Sport Sciences, 2022)
The purpose of this research is to understand the influence of sports lottery consumption motivation and sport spectators on sports participation behavior. In the present study, a total of 500 questionnaires were issued. Out of those, 479 valid questionnaires were returned. Self-compiled consumption motivation scale, sports spectators scale and sports participation behavior scale were used as research tools, with sports lottery ticket purchasers as the research object of the current study. The effective return rate is up to 95.8%. Followed by data collection, statistical analysis was done using various statistical tests which include, descriptive statistics, independent sample t test, single factor variance analysis and snow-fee method post-comparison, Pearson product difference correlation, multiple stepwise regression analysis and logistic regression. Conclusion: The overall consumption motivation of sports lottery consumers present a medium-level cognition situation. The sports spectators scale present a medium-to-low level situation, and the overall sports participation behavior-goal identity present a medium-to-high level cognition situation. Gender has a significant role with respect to entertainment factors and sports spectators in the consumption motivation factor dimension. Age has a significant role with respect to the public welfare factor in the consumption motivation factor dimension; education degree is in the consumption motivation factor dimension of economic factor, public welfare factor and sports spectators and sports participation behaviors-goal identification were found to be significantly different. Marriage had a significant difference in consumption motivation factor in terms of entertainment factor, public welfare factor and sports spectators and sports participation behaviors-goal identification; occupation is in consumption motivation factors economic factor, public welfare factors have reached a significant difference; monthly income has a significant difference in consumption motivation and sports spectators. Significant correlation was found between consumption motivation and sports appreciation. Consumption motivation had a positive effect on sports participation behavior-goal identification shows entertainment factor and public welfare factor; sports spectators show a positive influence on sports participation behavior-goal identification. Sports spectators had shown a significant relationship between sports participation behavior and actual participation.